BUNDA MARIA DAN GEREJA-GEREJA KRISTEN - Sabato, Salvatore (UNIKA Santo Thomas, 2005)
Through the Second Vatican Council the Catholic Church has renewed her teachings on Mary. It was done by treating out harmonically the true origins on the teachings such as the Bible, the writings of the Fathers of the Church and her tradition (pietas fidelium). The tradition enlivened by the Church for ages, is the proof of love for Jesus’ Mother and ours. There was a kind of symposium conducted by Catholic and Protestant theologians and experts in the Bible to find out the truth on Mary according to the Scripture and their common tradition. That is the reason why both denominations have to find the convergence in their teachings on Mary. Protestanism on its part needs to know precisely the teachings and attitudes of Reformators who do not see Mary as a scandal for ecumenical scene. The Catholic Church, on her part too, has to discover the proper position of Mary in the Scripture itself.